Magnesium Technology 2019 - Joshi, Vineet V.; Jordon, J. Brian; Orlov, Dmytro; Neelameggham, Neale R. (The Minerals, Metals & Materials Series,, 2019)
The Magnesium Technology Symposium, the event on which this collection is based, is one of the largest yearly gatherings of magnesium specialists in the world. Papers represent all aspects of the field, ranging from primary production to applications to recycling. Moreover, papers explore everything from basic research findings to industrialization. Magnesium Technology 2019 covers a broad spectrum of current topics, including alloys and their properties; cast products and processing; wrought products and processing; forming, joining, and machining; corrosion and surface finishing; and structural applications. In addition, there is coverage of new and emerging applications.